Assessment of online adaptive MR-guided stereotactic body radiotherapy of liver cancers. (September 2020) - Padgett, Kyle R.; Simpson, Garrett; Asher, David; Portelance, Lorraine; Bossart, Elizabeth; Dogan, Nesrin
Graphical abstract: Highlights: MRI provides superior visualization of abdominal anatomy compared to CBCT. MRgRT plan adaptation mitigates organ motion and provides superior dosimetry. Several patients had meaningful reductions in OAR violations with online adaptation. Not all liver SBRT patients materially benefit from online adaptation. Higher plan quality may permit safe dose escalation without compromising quality. Abstract: Purpose/objective: Online Adaptive Radiotherapy (ART) with daily MR-imaging has the potential to improve dosimetric accuracy by accounting for inter-fractional anatomical changes. This study provides an assessment for the feasibility and potential benefits of online adaptive MRI-Guided Stereotactic Body Radiotherapy (SBRT) for treatment of liver cancer. Materials/methods: Ten patients with liver cancer treated with MR-Guided SBRT were included. Prescription doses ranged between 27 and 50 Gy in 3–5 fx. All SBRT fractions employed daily MR-guided setup while utilizing cine-MR gating. Organs-at-risk (OARs) included duodenum, bowel, stomach, kidneys and spinal cord. Daily MRIs and contours were utilized to create each adapted plan. Adapted plans used the beam-parameters and optimization-objectives from the initial plan. Planning target volume (PTV) coverage and OAR constraints were used to compare non-adaptive and adaptive plans. Results: PTV coverage for non-adapted treatment plans was below the prescribed coverage for 32/47 fractions (68%), with 11 fractions failing by more than 10%. All 47 adapted fractions met prescribed coverage. OAR constraint violations were also compared for several organs. The duodenum exceeded tolerance for 5/23 non-adapted and 0/23 for adapted fractions. The bowel exceeded tolerance for 5/34 non-adaptive and 1/34 adaptive fractions. The stomach exceeded tolerance for 4/19 non-adapted and 1/19 for adaptive fractions. Accumulated dose volume histograms were also generated for each patient. Conclusion: Online adaptive MR-Guided SBRT of liver cancer using daily re-optimization resulted in better target conformality, coverage and OAR sparing compared with non-adaptive SBRT. Daily adaptive planning may allow for PTV dose escalation without compromising OAR sparing.